Pengaruh Edukasi Media Video dan Flipchart terhadap Motivasi dan Sikap Orangtua dalam Merawat Balita dengan Pneumonia - Harsismanto J; Suhendar Sulaeman (Jurnal Keperawatan Silampari, 2019)
This study aims to determine the effect of providing education with video media and flip charts on the motivation and attitudes of parents in caring for toddlers with pneumonia. This type of research is a quasi-experimental design with a non randomized without control group pretest-posttestdesign. The results showed there were differences in the average score of motivation and attitudes of parents in caring for toddlers with pneumonia before and after providing education. In the video media group Ï motivation value (0.001) and attitude (0,000), in the media group flip chart with Ï motivation value (0.002) and attitude (0,000) and in the video media and flip chart combination group with Ï motivation value (0,000) and attitude (0,000) . Conclusion, there is a significant influence of the use of educational media in providing education to an increase in the average score of motivation and attitudes of parents in caring for children with pneumonia. The combination of education using video media and flip charts gives more effective results than other education groups. Keywords: Supporting Media, Motivation, Health Education, Attitudes